Factors associated with diarrhea in children under five years old in the state of Pernambuco, according to surveys conducted in 1997 and 2006 - Maria Josemere de Oliveira Borba Vasconcelos; Anete Rissin; José Natal Figueiroa; Pedro Israel Cabral de Lira; Malaquias Batista Filho (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE Describe and compare variations of the factors associated with the prevalence of diarrhea in children under five years old in the state of Pernambuco. METHODS We used the databases of two population-based surveys from the years 1997 and 2006, with 2,078 and 1,650 children, respectively, evaluated in 18 municipalities of Pernambuco (Metropolitan Region of Recife, urban and rural interior). The variables, allocated at hierarchical levels, were analyzed using prevalence and Poisson regression ratios. RESULTS Only four variables were independently associated and were included in the final hierarchical model: geographical area, number of people per room, maternal age and the age of the child. In 1997: urban interior = 1.33 (95%CI 1.06-1.66), rural interior = 1.22 (95%CI 0.97-1.53) and in 2006: urban interior = 1.87 (95%CI 1.31-2.66), rural interior = 2.07 (95%CI 1.50-2.85); number of persons per room (1997): 1 to less than 2 = 1.29 (95%CI 0.98-1.68), two or more = 1.47 (95%CI 1.11-1.95) and in 2006: 1 to less than 2 = 0.86 (95%CI 0.68-1.09), two or more = 1.29 (95%CI 0.94-1.75); maternal age (1997): 10 to 19 years = 1.48 (95%CI 1.05-2.08), 20 to 24 years = 1.23 (95%CI 0.94-1.60), 25 to 34 years = 1.01 (95%CI 0.78-1.30) and in 2006: 10 to 19 years old = 1.70 (95%CI 1.08-2.66), 20 to 24 years old = 1.64 (95%CI 1.16-2.32), 25 to 34 years = 1.20 (95%CI 0.89-1.62); and age of the child (1997): 0-11 months = 1.57 (95%CI 1.27-1.94), 12-23 months = 1.73 (95%CI 1.41-2.12) and in 2006: 0-11 months = 1.04 (95%CI 0.76-1.41), 12-23 months = 1.77 (95%CI 1.41-2.23). CONCLUSIONS There was a great variability of the conditioners of diarrhea in children between the two periods analyzed. At the public policy level, despite changes in terms of people, time sequences, and geographic spaces, diarrhea remains on an important scale in the ranking of government power.